Globalization and Development : A Latin American and Caribbean perspective - Ocampo, José Antonio; Martin, Juan.; United Nations (Palo Alto, California : Stanford Social Sciences ; Washington, DC : World Bank, 2003)
Globalization and Development" draws upon the experiences of the Latin American and Caribbean region to provide a multidimensional assessment of the globalization process from the perspective of developing countries. Based on a study by the United Nations Economic Commission for Latin America and the Caribbean (ECLAC), this book gives a historical overview of economic development in the region and presents both an economic and noneconomic agenda that addresses disparity, respects diversity, and fosters complementarity among regional, national, and international institutions.
"Economic Commission for Latin America and the Caribbean"--Cover.
Includes bibliographical references (p. 179-199) and index.
rpm 08/09/2016
Loans
Keywords: Globalization; Economic development; Latin America; Caribbean Area